2019
DOI: 10.1111/dpr.12373
|View full text |Cite
|
Sign up to set email alerts
|

Information and communication technology adoption in micro and small firms: Can internet access improve labour productivity?

Abstract: The rapid spread of information and communication technologies (ICT) may increase firms’ productivity with important consequences for job creation and for economic growth. This article contributes to this discussion by analysing the impact of internet adoption on labour productivity and the mechanisms shaping this relationship in Peruvian micro and small manufacturing firms over the period 2011–2013. The article estimates a reduced form where labour productivity is a function of internet adoption and other exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…The number of employees has a positive effect, thus, the greater the number of employees working in the company, the greater the willingness to embrace ICTs. This result is aligned with research by Lucchetti and Sterlacchini (2004), Galliano and Roux (2008), Battisti and Stoneman (2005), Khalifa (2016), Loukis, Arvanitis, and Kyriakou (2017) and Viollaz (2018), where it is shown that the larger the company, usually measured through the number of employees, the greater the willingness there is to adopt computer and communication technologies, and this is contrary to the work of Hollenstiein ( 2004) and Meyer (2011).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The number of employees has a positive effect, thus, the greater the number of employees working in the company, the greater the willingness to embrace ICTs. This result is aligned with research by Lucchetti and Sterlacchini (2004), Galliano and Roux (2008), Battisti and Stoneman (2005), Khalifa (2016), Loukis, Arvanitis, and Kyriakou (2017) and Viollaz (2018), where it is shown that the larger the company, usually measured through the number of employees, the greater the willingness there is to adopt computer and communication technologies, and this is contrary to the work of Hollenstiein ( 2004) and Meyer (2011).…”
Section: Resultssupporting
confidence: 84%
“…The age of the owner also has a negative sign, thus, the older they are, the lower the probability of adoption, since for each additional year the probability decreases by 0.7%. Regarding the previous variables, in the research by Viollaz (2018), it is found that the age of the company administrator does not show statistical signi cance, and if he is male, the probability increases. This last nding is different from the result obtained here.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In Italy, Colombo et al ( 2013 ) examined the effect of ICTs on productivity of small and medium enterprises (SMEs) and found that adopting advanced ICTs had a positive effect on SMEs’ productivity. With regard to labor productivity, some researchers found that access to the Internet improved firm labor productivity and expanded total employment, especially for micro and small firms (Paunov & Rollo, 2016 ; Viollaz, 2019 ). This is because adopting ICTs results in the formalization of a labor relationship, which improves labor productivity.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Internet availability in Brazil did not affect overall employment and even affect the demand of low-skilled workers by replacing routine tasks (Almeida, Corseuil, & Poole, 2017;Dutz, Mation, O'Connell, & Willig, 2017). Similarly, Internet adoption in Peru increased the demand for production workers with permanent contracts and decreased the demand for administrative workers with temporary contracts and non-remunerated workers (Viollaz, 2018). In Chile, the adoption of complex software increased the share of administrative and unskilled production workers and reduced the share of skilled production workers (Almeida, Fernandes, & Viollaz, 2017).…”
Section: New Technology and Labor Demandmentioning
confidence: 99%